2023
DOI: 10.1002/advs.202205093
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneously Right‐Side‐Out‐Orientated Coupling‐Driven ROS‐Sensitive Nanoparticles on Cell Membrane Inner Leaflet for Efficient Renovation in Vascular Endothelial Injury

Abstract: Biomimetic cell membrane camouflaged technology has drawn extensive attention as a feasible and efficient way to realize the biological functions of nanoparticles from the parent cells. As the burgeoning nanotherapeutic, the right-side-out orientation self-assembly and pathological dependent "on-demand" cargo release of cell membrane camouflaged nanocarriers remarkably limit further development for practical applications. In the present study, a spontaneously right-side-out-orientated coupling-driven ROS-sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 51 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…The blood compatibility of MM@DA-pCD@MTX was assayed in vitro using a direct contact assay as previously reported. 33 0.1 mL portion of whole blood was, respectively, added into free MTX, DA-pCD@MTX NPs, or MM@ DA-pCD@MTX solution with the same concentration (MTX as 100 μg/mL). The absorbance of the supernatant was measured.…”
Section: Preparation Of MM Coating Nanoparticlesmentioning
confidence: 99%
“…The blood compatibility of MM@DA-pCD@MTX was assayed in vitro using a direct contact assay as previously reported. 33 0.1 mL portion of whole blood was, respectively, added into free MTX, DA-pCD@MTX NPs, or MM@ DA-pCD@MTX solution with the same concentration (MTX as 100 μg/mL). The absorbance of the supernatant was measured.…”
Section: Preparation Of MM Coating Nanoparticlesmentioning
confidence: 99%
“…The implementation of a right-side-out-orientated coating holds signicant importance in advancing the research and applications of cell membrane camouaging nanotherapeutics. 1,2 By preserving the intrinsic structure and functionality of the cell membrane, including pivotal elements like surface receptors and signal transduction pathways, this approach bestows amplied effectiveness upon the camouage, enabling precise recognition and targeting capabilities. 3 Moreover, it serves to mitigate immune rejection responses, thereby improving the overall biocompatibility and stability of the nanoparticles encapsulated within the right-side-out-orientated cell membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is an ideal case to improve the development of a novel and viable strategy to achieve efficient cell membrane coating, particularly when confronted with situations lacking suitable affinity between certain cell membrane and core pairs. To address this critical issue, our previous research has revealed that the specic binding between the intracellular domain of the transmembrane protein band 3 in red blood cells (RBCs) and the P4.2 peptide ligand can effectively guide the encapsulation of cell membranes with the desired right-side-out orientation, 1 addressing the deciencies of the traditional preparation techniques such as co-extrusion 4,5 or ultrasound. 6,7 However, it is important to note that the highly specic nature of the transmembrane protein band 3 restricts its applicability to the right-side-out orientation encapsulation of RBC membranes alone, resulting in it being unadaptable for a diverse range of biomimetic cell membrane carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Intravenous injection is the major route of administration of living cell carriers [10][11][12] , and cells in the blood are exposed to a complex blood ecosystem, including massive amounts of blood cells and fluid shear stress (FSS) induced by the blood flow [21][22][23] . Living cells will experience several different levels of FSS when they stay in blood circulation 22 .…”
Section: Introductionmentioning
confidence: 99%